Strategi Pemasaran Warung Roti Bakar Jamil dalam Meningkatkan Daya Saing Bisnis Kuliner di Bandar Lampung - Nadia Mirsa Aprilia (Bulletin of Community Engagement, 2024)
A marketing strategy is basically a comprehensive, integrated and integrated plan in the field of marketing, which provides guidance on the activities that will be carried out to achieve a company's goals. The aim of this research is to find out the strategies used by the Jamil toast stall to increase the competitiveness of the culinary business, especially in Bandar Lampung. This research uses qualitative research methods. Data collection is through interviews, namely searching for information created from questions from respondents (sources of information). The analysis used is a qualitative method, namely analysis of marketing strategies in all branches of Jamil toast stalls to increase sales success. In increasing the competitiveness of Bandar Lampung's Jamil toast stall, it has used a good marketing strategy. Because in the Marketing Strategy of Jamil Toast Stall, the marketing mix strategy is used to simplify and streamline marketing activities so that Jamil Toast Stall can compete with competitors who have the same business. It can be concluded overall that the quality of the products sold by the Jamil toast stall always pays comprehensive attention to the aspects of freshness of raw materials, taste, portions and the condition of the food in good condition. The aim is that the Jamil toast shop can guarantee consumer satisfaction. Furthermore, for unstable raw material prices, Jamil Toast Stall always maintains product prices by adjusting the portion of toast served. Maintain prices and adjust portions. And to increase the competitiveness of Jamil's toast stall, it has been carrying out promotions so far, namely offline and online. Where the promotion used is word of mouth and face to face with consumers as well as printing brochures including contacts and offers on social media in the form of posts. As well as a strategic location according to the target market which is the route for students, pupils and the public so that it can make it easier for the Jamil toast stall to attract consumer interest.